PELATIHAN PENYUSUNAN PITCH DECK DAN MITIGASI RISIKO BAGI PENGURUS KOPERASI DESA MERAH PUTIH DI KABUPATEN BANYUMAS - Tissa Silvia; Ranjani Ranjani (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
Cooperatives are a strategic pillar of the people's economy for village economic independence, yet they often face obstacles in capital expansion and managerial resilience. The Merah Putih Village Cooperative in Banyumas Regency experienced stagnation due to conventional management patterns and limited management competence in communicating business potential to external partners. This community service activity aims to increase management capacity through the integration of proactive strategies in the form of pitch deck preparation and defensive strategies in the form of risk mitigation. The method used is Participatory Technological Development (PTD) which includes the stages of problem identification, educational workshops, guided practical assistance, and evaluation using pre-test and post-test questionnaires. The results show a significant transformation in the management's financial and digital literacy, validated by an average score increase of 45%. Beyond technical improvements, this activity triggered a mindset shift among managers into visionary social business managers, capable of constructing accountable business narratives and systematically identifying critical operational risk points. The synergy between business negotiation skills and risk management serves as a prototype for professional, transparent, and competitive rural cooperative governance in Banyumas Regency. Keywords: Village Cooperative; Pitch Deck, Risk Mitigation, Economic Empowerment, Banyumas